Multi-criterion comparative analysis – tool for the functional quality assessment of flats: Part I. The base of conducted examinations - Jezierski, Walery; Kłopotowski, Maciej; Gromadzka, Anna (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2016)
Choosing (buying) flats is a multistage, complicated decision which many elusive factors affect. Mathematical methods allow for construction of the measuring tool letting for making these processes more objective. It requires distinguishing features affecting the decision making in this process by specific groups of users and determining their importances.